2014
DOI: 10.1177/0972266120140203
|View full text |Cite
|
Sign up to set email alerts
|

Strategies and Policies for Alleviation of Rural Poverty in India: Experience of Mahatma Gandhi National Rural Employment Guarantee Scheme

Abstract: Eradication of rural poverty has been a continuing quest of the planning-led development process in India. A plethora of development delivery institutions has emerged over the years to benefit the poor and the disadvantaged groups of the society, and thereby to promote inclusive growth of the economy. The Central government and different state governments have introduced a number of such development delivery institutions to alleviate rural poverty in the country. The Mahatma Gandhi National Rural Employment Gu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
(26 reference statements)
0
1
0
Order By: Relevance
“…8 Further, the performance of the MGNREGA has deteriorated over the years . However, the experiences at the state level have been mixed (Mishra and Mishra 2015). It is observed that higher utilization of available funds in these states did not have any significant impact on physical performance of the scheme (Table 7.…”
Section: Performance Of Mgnrega In Odisha and West Bengal: An Overviewmentioning
confidence: 99%
“…8 Further, the performance of the MGNREGA has deteriorated over the years . However, the experiences at the state level have been mixed (Mishra and Mishra 2015). It is observed that higher utilization of available funds in these states did not have any significant impact on physical performance of the scheme (Table 7.…”
Section: Performance Of Mgnrega In Odisha and West Bengal: An Overviewmentioning
confidence: 99%